Leveling the playing field for less-sophisticated non-professional investors: Does plain English matter? - Eileen Taylor; Jennifer Riley (Journal of Capital Markets Studies (JCMS), 2017)
Purpose - The purpose of this paper is to explore how non-professional investors (NPIs) with varying levels of financial sophistication interpret and perceive corporate disclosures and management credibility, specifically risk factors, when those disclosures are presented in readable and less-readable formats. Design/methodology/approach - The paper uses an online experiment to test hypotheses related to the effects of financial sophistication (measured) and readability (manipulated) on NPIs' equity valuations and perceptions of management credibility (competence and trustworthiness). Findings - Increased readability appears to counteract less-sophisticated NPIs' conservatism in equity valuations, such that they are not statistically significantly different from more-sophisticated NPIs' equity valuations. Further, less-sophisticated NPIs judge management as less competent when disclosures are less readable, while more-sophisticated NPIs judge management as more competent when disclosures are less readable. Research limitations/implications - The paper has important implications for the SEC's regulations related to plain English requirements for risk factor and other corporate disclosures. Financial sophistication varies among NPIs, and readability appears to influence these individuals in different ways. Practical implications - The SEC's Concept Release (April 13, 2016) acknowledges the need to update and improve risk factor disclosure regulations. This study provides evidence that contributes to those decisions. Originality/value - The paper extends the research on processing fluency, by examining readability of disclosures with a consistent tone (negative). The NPIs surveyed are directly representative of the population of interest for risk factor disclosure regulations.
Keywords: 330; Risk factor; Processing fluency; Corporate disclosures; Regulation S-K; Non-professional investor